ENHANCING BRAND LOYALTY AT UNIQLO: THE ROLE OF STORE ATTRIBUTES, CUSTOMER EXPERIENCES, AND ENGAGEMENT - Salma Nurhaliza; Indrawati Indrawati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
There was a phenomenon of an increase in number of e-commerce users, mobile applications, and other digital technologies, most consumers still prefer to shop in offline stores for various reasons. The biggest factor for consumers choosing to shop offline, with the largest percentage of 62%, is the desire to physically inspect the goods. Retailers should enhance in-store experiences by implementing responsive and innovative store attributes. This research aims the impact of store attributes on brand loyalty, with customer engagement as mediating variables. Using a quantitative, causal-descriptive analysis, data was collected from 280 qualified respondents through purposive sampling. The study employs Structural Equation Modeling (SEM) based on Partial Least Square (PLS) analysis using Smart-PLS 3.0 software. Results indicate a positive and significant influence of merchandise, transaction convenience, loyalty program and customer engagement on brand loyalty. It also shows that customer experience and engagement mediate the relationship between store attributes and brand loyalty. The model explains 42% of the variance in Uniqlo's brand loyalty, which falls into the moderate category.